2021
DOI: 10.1097/mlr.0000000000001548
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Patient Experience Between Primary Care Settings Tailored for Homeless Clientele and Mainstream Care Settings

Abstract: Background: More than 1 million Americans receive primary care from federal homeless health care programs yearly. Vulnerabilities that can make care challenging include pain, addiction, psychological distress, and a lack of shelter. Research on the effectiveness of tailoring services for this population is limited.Objective: The aim was to examine whether homeless-tailored primary care programs offer a superior patient experience compared with nontailored ("mainstream") programs overall, and for highly vulnera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…These services have been incorporated successfully using a "one-stop-shop" strategy for different types of health and social care, or through the use of an outreach model of care. This concept was reported as a strength of many healthcare interventions targeted to individuals experiencing homelessness (Kertesz et al, 2021;Luchenski et al, 2018;Magwood et al, 2020). In a program serving veterans who are homeless, comparing regular health services to an integrated program that included primary care, social services, and mental health services demonstrated that patients who attended the integrated service had higher usage of primary care services and reduced usage of emergency services (McGuire et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…These services have been incorporated successfully using a "one-stop-shop" strategy for different types of health and social care, or through the use of an outreach model of care. This concept was reported as a strength of many healthcare interventions targeted to individuals experiencing homelessness (Kertesz et al, 2021;Luchenski et al, 2018;Magwood et al, 2020). In a program serving veterans who are homeless, comparing regular health services to an integrated program that included primary care, social services, and mental health services demonstrated that patients who attended the integrated service had higher usage of primary care services and reduced usage of emergency services (McGuire et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…This study utilized data from a national survey of homelessexperienced Veterans completed between April and October of 2018, carried out under contract by a professional survey organization, Strategic Research Group of Columbus, Ohio, to the VA as part of a broader funded research study. [17][18][19] The primary aim of the survey was to compare care experience between primary care delivered in clinics that were tailored for clientele with recent homeless experience to care in nontailored clinics. As described in greater detail elsewhere, 17 survey eligibility was based on VA records indicating receipt of services or diagnostic codes that indicated a history of homelessness, and 2 or more visits to a primary care clinic in the prior 2 years.…”
Section: Methodsmentioning
confidence: 99%
“…This study utilized data from a national survey of homeless‐experienced Veterans completed between April and October of 2018, carried out under contract by a professional survey organization, Strategic Research Group of Columbus, Ohio, to the VA as part of a broader funded research study 17–19 . The primary aim of the survey was to compare care experience between primary care delivered in clinics that were tailored for clientele with recent homeless experience to care in nontailored clinics.…”
Section: Methodsmentioning
confidence: 99%
“…Recent research focuses on whether tailoring services for the homeless experience can engage and improve care for this population (Gabrielian et al, 2017; O'Toole et al, 2016). Such efforts to tailor care include a Veterans Health Administration (VHA) clinic paradigm, called Homeless Patient Aligned Care Teams (H‐PACTs), which may improve patient experience and satisfaction (Kertesz et al, 2021). The VHA is the largest integrated healthcare system in the U.S., providing health and social services for 9 million Veteran enrollees across 179 medical centres and 1245 outpatient clinics.…”
Section: Introductionmentioning
confidence: 99%